Effects of performance level in biathlon-specific shooting tests - Luchsinger, H.; Kocbach, J.; Sandbakk, O. (NVC Conference 2017, 5.-6. October 2017, Are, Sweden, 2017)
Shooting performance is a crucial component for the overall result in biathlon competitions. The knowledge about the effects of various shooting-specific capacities on shooting performance would be of high value for coaches and athletes. Thus, the aim of the current study was to compare biathlon-specific shooting tests between competitive biathletes on different performance levels.